Ireland: A Cautionary Tale About Free Tuition - Hauptman, Arthur (International Higher Education, 2021)
Irish higher education has had a mixed experience since 1995, when tuition was eliminated for full-time undergraduates. Enrollments have doubled, the completion rate has remained high, and the attainment rate has tripled (although mostly a function of well-educated foreign workers settling in Ireland). But equity remains a problem and boom-and-bust funding tied to the economy has contributed to quality concerns. Lessons for countries considering free tuition regimens include that sustained funding is critical to success.